HUBUNGAN ANTARA TINGKAT KETERGANTUNGAN PASIEN DENGAN KEBUTUHAN TENAGA KEPERAWATAN DI IRNA PENYAKIT DALAM RSUD SRAGEN - Indriyastuti, Nurul; Muhlisin, Abi (Universitas Muhammadiyah Surakarta, 2008)
In this research the writer tries to research about how far the relation ship between the dependence of the patients and the need of the nursing man power in IRNA Internal disease in the Regional Publik Hospital of Sragen. The purpose of this research is to get to know the relation ship between the dependence of the patients and the need of the nursing man power. The research was carried out in IRNA Internal disease of theRegionalPublicHospitalin Sragen, with 48 samples of people with the whole population of the data gathering methode using questioner. The data analysis methode used is the spearman corelation analysis as the kind of the data is ordinal. The results of the data and the need of the â€œmorningâ€ nursing man power can be acknowledged that the corelation between the dependence of the patients and the need of the nursing man power is significant, while the corelation number is positive (0,313), means the more patients, the more the nursing man power needed. The result of the calculation and the data analysis of the need of thenoonnursing man power is noted that the corelation between the dependence of patient and the need of the nursing man power is significant. Meanwhile, the correlation number is positive (0,474), means the more patients, the more the nursing man power needed. The result of the data research is that the night nursing man power, the corelation of the dependence of the patients and the need of the nursing man power is significant, while the corelation is positive (0,285), the more patients, the more nursing man power needed. The conclucion is that there is a corelation between the dependence of the patients and the need of the nursing man power. The strongest relation ship is the need of the shift of the nursing man power with the corelation number of 0,574.Â